Comparison of the Predictive Ability of the Blood Urea Nitrogen/Albumin, C-Reactive Protein/Albumin, and Lactate/Albumin Ratios for Short-Term Mortality in SARS-CoV-2-Infected Patients - Özdemir, Serdar; Altunok, İbrahim (Avicenna Journal of Medicine, 2023)
Background Hematological parameters and their ratios are the most studied biomarkers for prediction of mortality or severe illness in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. This study aims to compare the power of the blood urea nitrogen (BUN)/albumin ratio, lactate/albumin ratio, and C-reactive protein (CRP)/albumin ratio, measured at the time of admission, in predicting 30-day mortality in SARS-CoV-2-infected patients presenting to the emergency department (ED).Materials and Methods This retrospectively designed, single-center, observational study was performed in the ED of a tertiary education health care center. We documented the data of patients admitted with a confirmed SARS-CoV-2 infection between September 1, 2020, and January 1, 2021.Results Of the 470 patients included in the study, 232 (49.4%) were female. The all-cause 30-day mortality rate was 23.8%. The area under the curve values for the BUN/albumin ratio, lactate/albumin ratio, and CRP/albumin ratio in the prediction of 30-day mortality were 0.725, 0.641, and 0.749, respectively. Sensitivity and negative predictive value for CRP/albumin ratio (≥0.049) and specificity for BUN/albumin ratio (≥1.17) were 92.86, 94.9, and 71.23, respectively. The odds ratio values of the BUN/albumin ratio (≥1.17), CRP/albumin ratio (≥0.049), and lactate/albumin ratio (≥0.046) for 30-day mortality were determined as 4.886, 9.268, and 2.518, respectively.Conclusion The BUN/albumin ratio and CRP/albumin ratio can be used to predict 30-day mortality in SARS-CoV-2-infected patients admitted to ED. Furthermore, CRP/albumin ratio had the highest sensitivity and negative predictive value, while BUN/albumin ratio had the highest specificity.
Keywords: biomarkers; albumin; C-reactive protein; SARS-CoV-2; coronavirus disease 2019; blood urea nitrogen